Technical guide of reflection on the mechanisms for disseminating climate information - Ogou, Anani; Ouedraogo, Mathieu; Laderach, Peter (2024)
As part of the technical assistance of the Alliance of Bioversity International and CIAT for the implementation of the project to strengthen agricultural productivity and climate resilience (ProPAD) in CHAD, one of the major activities was to set up a mechanism for the dissemination of climate information, to the benefit of producers in the provinces of Salamat, Mandoul and Moyen Chari in Chad. In order to take into account, the aspirations of grassroots stakeholders, this guide was designed to help stakeholders during a workshop organized for this purpose. This guide seeks to bring together in working groups, actors coming from the same area who have more or less knowledge of the actual facts of the project area. This might lead to taking into consideration the realities on the ground by involving key stakeholders, particularly representatives of producer organizations, meteorological services, extension services, ministries in charge of agriculture and the environment, NGOs, national agricultural research institutes, project and program management teams, etc. This guide is focused around nine key questions leading to simple and realistic diagrams. The questions contained in this guide are not exhaustive. They can be adapted to each context of the project by any user.